Nepal-China Military Relation - Basnyat, Laxmi (Voice of History, 2023)
Any military relation with government to government or International or Regional Organizations would be the part of National Diplomacy and interests. In other words, it is Track Two diplomacy after Track One Diplomacy of the government. Bilateral Military relations consists of those activities of a government which are primarily concerned with its armed forces and development assistances too. The histories of bilateral military relations would be sweet and sour. Accordingly, Nepal-China military realties consists of many confrontations and supports. Nepal-China relation is a milestone in the diplomatic history of Nepal. Diplomatic relation is the combination of economic, trade and transit, cultural, military and many more aspects. Nepal – China (Sino-Nepal) Military Relation also begins since our diplomatic history with China. Any diplomatic movement and strategy directly relate with personal security and National security. Nepal –China Relations has two folds; Nepal used to have separate diplomatic relations with China and Tibet up to October 1950. So far, China claims that Tibet was its own part always and never an independent. We could find some events in Sino – Nepal Military relation. Which have been written in many documents, books, and journals. However, an exact document, proofs, archives lack to cover Sino-Nepal Military Relation from ancient period onwards. Background of Sino - Nepal relation, Nepal –Tibet Wars, Nepal –China War, are the main aspects to be highlighted. This article would be based on Qualitative research design applying secondary sources and interpretation of data is content analysis as well as based on Bilateral Relation Theory. Finding of the research paper is to create the separate domain as Nepal-China military relation based on military perspective. The limitation of this paper would be the only major bilateral military confrontations after 1744.